Proteomic analysis revealed that the oomyceticide phosphite exhibits multi-modal action in an oomycete pathosystem - Andronis, Christina E.; Jacques, Silke; Lopez-Ruiz, Francisco J.; Lipscombe, R.; Tan, Kar-Chun (2024)
Phytopathogenic oomycetes constitute some of the most devastating plant pathogens and cause significant crop and horticultural yield and economic losses. The phytopathogen Phytophthora cinnamomi causes dieback disease in native vegetation and several crops. The most commonly used chemical to control P. cinnamomi is the oomyceticide phosphite. Despite its widespread use, the mode of action of phosphite is not well understood and it is unclear whether it targets the pathogen, the host, or both. Resistance to phosphite is emerging in P. cinnamomi isolates and other oomycete phytopathogens. The mode of action of phosphite on phosphite-sensitive and resistant isolates of the pathogen and through a model host was investigated using label-free quantitative proteomics. In vitro treatment of sensitive P. cinnamomi isolates with phosphite hinders growth by interfering with metabolism, signalling and gene expression; traits that are not observed in the resistant isolate. When the model host Lupinus angustifolius was treated with phosphite, proteins associated with photosynthesis, carbon fixation and lipid metabolism in the host were enriched. Increased production of defence-related proteins was also observed in the plant. We hypothesise the multi-modal action of phosphite and present two models constructed using comparative proteomics that demonstrate mechanisms of pathogen and host responses to phosphite. Significance: Phytophthora cinnamomi is a significant phytopathogenic oomycete that causes root rot (dieback) in a number of horticultural crops and a vast range of native vegetation. Historically, areas infected with phosphite have been treated with the oomyceticide phosphite despite its unknown mode of action. Additionally, overuse of phosphite has driven the emergence of phosphite-resistant isolates of the pathogen. We conducted a comparative proteomic study of a sensitive and resistant isolate of P. cinnamomi in response to treatment with phosphite, and the response of a model host, Lupinus angustifolius, to phosphite and its implications on infection. The present study has allowed for a deeper understanding of the bimodal action of phosphite, suggested potential biochemical factors contributing to chemical resistance in P. cinnamomi, and unveiled possible drivers of phosphite-induced host plant immunity to the pathogen.